Step-by-step explanation:
hhgfffhbytyyhhyyyhhghgvgbgb
Length (2, 6) to (-4, 6) is sqrt((x2 - x1))^2 + (y2 - y1)^2) = sqrt((-4 -2)^2 + (6 - 6)^2) = sqrt((-6)^2 + 0) = 6
Length (2, 6) to (-4, 4) is sqrt((-4 - 2)^2 + (4 - 6)^2) = sqrt((-6)^2 + (-2)^2) = sqrt(36 + 4) = sqrt(40) = 2sqrt(10) units
Length (-4, 6) to (-4, 4) is sqrt((-4 - (-4))^2 + (4 - 6)^2) = sqrt(0^2 + (-2)^2) = 2
So the length of the longest side is 2sqrt(10) units
Answer:
1. 4.5
Step-by-step explanation:
3 x 1.5 = 3 x 1 1/5 = 4.5
Answer:
x = 45 degrees
Step-by-step explanation:
Those angles are equal, so set:
2x + 6 = 96
2x = 90
x = 45
(46/3)-6=9
Her daughter is 9 years old and her mother is 37.